Efektivitas Metode Resitasi Terhadap Hasil Belajar Matematika Siswa Kelas VIII Mtsn 4 Bojonegoro - Eka Wahyu Ningtiyas; Arum Dwi Rahmawati; Anwas Mashuri (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
Mathematics learning in MTsN 4 Bojonegoro is less effective, especially on the subject of circles. This is because in the learning process they still use conventional methods or lectures. So that this study is based on the researcher's interest in applying the recitation method to the learning process in MTsN 4 Bojonegoro. The problem in this study is: which is more effective between learning with the recitation method or conventional learning on the mathematics learning outcomes of grade VIII students on the subject of the MTsN 4 Bojonegoro circle for the 2023/2024 academic year. This research aims to find out: the effectiveness of the recitation method on learning outcomes mathematics for class VIII students on the subject of the MTsN 4 Bojonegoro circle for the 2023/2024 academic year. The population of this study were class VIII students in semester 2 of MTsN 4 Bojonegoro who were divided into seven classes. Sampling was carried out using a cluster random sampling technique, class VIII A students were obtained as the experimental class, while the control class was class VIII D. In the experimental group learning used the recitation method, while the control group used the conventional method (lecture).